2007
DOI: 10.1097/gim.0b013e318159a37c
|View full text |Cite
|
Sign up to set email alerts
|

Stage II follow-up on a linkage scan for bipolar disorder in the Ashkenazim provides suggestive evidence for chromosome 12p and the GRIN2B gene

Abstract: Purpose: We had previously performed a genome-wide linkage scan for bipolar affective disorder in an Ashkenazi Jewish sample, a population likely to have reduced genetic heterogeneity. This study is a second stage follow-up focusing on regions that showed positive linkage scores in our previous scan but were not fine-mapped at that time. Methods:We genotyped an additional 145 highly polymorphic microsatellites and conducted linkage analyses using standard laboratory and analytical methods. Results: We saw an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Our results, even if preliminary, are consistent with previous positive findings in the literature showing the role of chromosome 12 in susceptibility to bipolar disorders [23,25] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results, even if preliminary, are consistent with previous positive findings in the literature showing the role of chromosome 12 in susceptibility to bipolar disorders [23,25] .…”
Section: Discussionsupporting
confidence: 83%
“…It encodes for a subunit of the NMDA receptor, an ionotropic glutamate receptor. This receptor is a heteromeric pentamer composed of at least 1 NR1 subunit and 1 or more of the 4 different NR2 subunits: NR2A, NR2B (the product of GRIN2B), NR2C and NR2D [23] . There are already important evidences for an association between this gene and Huntington disease, epilepsy, dementia and also schizophrenia and bipolar disorder [3,[40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene is a member of metabotropic glutamate receptors, which is mediated by a G-protein-coupled second messenger system involved in the central action of glutamate (Marin and Chen 2004;Namkoong et al 2007). Another, some reports indicated GRIN2B, a member of ionotropic glutamate receptors, is related to obsessive-compulsive disorder, schizophrenia, bipolar disorder, and some other psychotic disorders (Martucci et al 2006;Avramopoulos et al 2007;Arnold et al 2009). Of the 5-HT receptors, the 5-HT2A gene is involved in the development of temperament and borderline personality disorder (Jokela et al 2007;Soloff et al 2007) and the 5-HT6 gene roles in differences in novelty-seeking behavior (Ballaz et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…21 Associations have been observed between several polymorphisms in the GRIN2B gene and the 12p13.1-p12.3 region (containing the GRIN2B gene) and BD. 16,22,23 Miyatake et al have observed that the T allele of the GRIN2B rs1019385 SNP results in increased luciferase transporter activity in the presence of nerve growth factor (NGF). 24 The presence of a G allele had no effect on reporter activity, suggesting that GRIN2B rs1019385 may have a role in transcriptional control of the GRIN2B transcript.…”
Section: Introductionmentioning
confidence: 99%